Low and ultra-low-cycle fatigue behavior of X52 piping steel based on theory of critical distances. (May 2020) - Pereira, J.C.R.; de Jesus, A.M.P.; Xavier, J.; Correia, J.A.F.O.; Susmel, L.; Fernandes, A.A.
Highlights: ULCF/LCF is characterized for X52 pipeline steel by smooth and notched specimens. The theory of critical distances is applied with point, line and area methods. Point method revealed to be the most appropriate for correlating ULCF and LCF data. Proposed TCD/PM successfully predicted notch bending ULCF test data. Abstract: The cyclic failure observed in structural components such as pipelines subjected to extreme loading conditions highlights some limitations concerning the application of existing fatigue damage models. The evaluation and prediction of this type of failure in these steel components under large-scale plastic yielding associated with high levels of stress triaxiality are not sufficiently known nor explored. This fatigue domain is conventionally called ultra-low-cycle fatigue (ULCF) and damage features are representative of both low-cycle fatigue (LCF) and monotonic ductile fracture. Thus, in order to understand the ULCF damage mechanisms both monotonic and LCF tests are required to get representative bounding damage information to model the material damage behaviour under such extreme loading conditions. This paper aims at exploring the Theory of Critical Distances (TCD) in the LCF and ULCF fatigue regimes, including the application of the point, line and area methods. The application of the TCD theories has not been explored so far in the ULCF fatigue regimes, despite its promising results in the LCF and high-cycle fatigue. An experimental program was carried out on several specimens' geometries made of X52 piping steel. In detail, smooth plane specimens and notched plane specimens were cyclic loaded under tension/compression loading in order to obtain fatigue lives within the range of 10 1 –10 4 cycles. In addition, cyclic bending tests on notched plane specimens were also incorporated in this study. Finite element simulations of all small-scale tests were conducted allowing to derive elastoplastic stress/strain fields along the potential crack paths. The numerical data were subjected to a post-processing in order to find characteristic lengths that can be treated as a fatigue property according to the TCD. A unified strain-life relation is proposed for the X52 piping steel together with a characteristic material length, consisting of a practical relation for pipeline strain-based design under extreme cyclic loading conditions.